Cytoskeleton-associated large RNP complexes in tobacco male gametophyte (EPPs) are associated with ribosomes and are involved in protein synthesis, processing, and localization - Honys, David; Rĕnák, David; Feciková, Jana; Jedelský, Petr L; Nebesárová, Jana; Dobrev, Petre; Capková, Vĕra (Journal of proteome research, 2009)
The progamic phase of male gametophyte development involves activation of synthetic and catabolic processes required for the rapid growth of the pollen tube. It is well-established that both transcription and translation play an important role in global and specific gene expression patterns during pollen maturation. On the contrary, germination of many pollen species has been shown to be largely independent of transcription but vitally dependent on translation of stored mRNAs. Here, we report the first structural and proteomic data about large ribonucleoprotein particles (EPPs) in tobacco male gametophyte. These complexes are formed in immature pollen where they contain translationally silent mRNAs. Although massively activated at the early progamic phase, they also serve as a long-term storage of mRNA transported along with the translational machinery to the tip region. Moreover, EPPs were shown to contain ribosomal subunits, rRNAs and a set of mRNAs. Presented results extend our view of EPP complexes from mere RNA storage and transport compartment in particular stages of pollen development to the complex and well-organized machinery devoted to mRNA storage, transport and subsequent controlled activation resulting in protein synthesis, processing and precise localization. Such an organization is extremely useful in fast tip-growing pollen tube. There, massive and orchestrated protein synthesis, processing, and transport must take place in accurately localized regions. Moreover, presented complex role of EPPs in tobacco cytoplasmic mRNA and protein metabolism makes them likely to be active in another plant species too. Expression of vast majority of the closest orthologues of EPP proteins also in Arabidopsis male gametophyte further extends this concept from tobacco to Arabidopsis, the model species with advanced tricellular pollen.
Keywords: proteosyntéza; Protein Biosynthesis; Germ Cells; ribonukleoproteiny; cytoskelet; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; rostlinné proteiny; Chromatography, High Pressure Liquid; Ribosomes; Plant Proteins; tabák; vysokoúčinná kapalinová chromatografie; spektrometrie hmotnostní - ionizace laserem za účasti matrice; ribozomy; Pollen Tube; Pollen; Cytoskeleton; pylová láčka; zárodečné buňky; Ribonucleoproteins; Nicotiana; pyl